Asian financial crisis, restructuring and implications for financial sector's reform in Vietnam - Nguyen, Khanh Tuan (KDI School, 2000)
Vietnam benefits from both the success's and failure's experiences of other countries in the region on the road to development especially in the transition process from a relatively closed economy with rudimentary, repressed financial system toward a market-based open financially economy. The thesis briefly traces the financial liberalization, crisis and restructuring in East Asian countries, namely Thailand, Indonesia and Korea and attempts to discuss some issues and lessons that seem beneficial to further the process of financial sector's reform in Vietnam. The thesis consists of four chapters. Chapter I begins with an introduction of purposes, scope, methods and content of the thesis. Chapter II, comparative countries analysis and descriptive inference with supports from relevant studies will be employed to underscore the weaknesses of the banking and financial sector, inadequate financial supervision and regulations, ill prepared financial liberalization and vulnerable exchange regime, which rendered the system vulnerable to a sudden withdrawal of investors' confidence. When it occurred, the crisis was the result. The ongoing restructuring in these countries is quite complex but provides a general framework to address these weaknesses and to build a robust domestic financial system. Chapter III, time series data analysis and overall financial soundness indicators of state-owned enterprises and the banking sector will be used to assess the economic performance in the last decade and the ongoing reform of the financial sector in Vietnam. In light of the lessons and experiences abstracted from elsewhere in the region, the thesis highlights the weaknesses of the current system, which in many ways are similar to those in other countries. This thesis also discusses some measures to address these weaknesses. Chapter IV briefly analyzes the recent recovery and development of Vietnamese economy and its impacts on the financial system. To further the financial sector reform, the conclusion part discusses some suggestions regarding strengthening banking regulations and supervision, interest rate liberalization and once again, highlights the lessons from the region financial crisis with implications for mitigating the adverse consequences of such reform and liberalization of the financial sector in Vietnam.
Thesis(Master) --KDI School:Master of Public Policy,2000